Socio-economic background of University students of Sri Lanka - Jayawardhana, Ananda (My University, 2012)
University education was expanded in Sri Lanka due to free education. University education was converted to the poor community from elites. Students who attend to the Universities were expanded. But the limited Universities do not absorb all qualified students. By 1955 students who were working class less number entered Universities. At present farther of University students 70% came from working class. More than 80% of students from rural areas. 70% of farthers of University students are G.C.E. (O/L) qualified and 60% of mothers are non employees. More families have no extra income and 52% student get "Mahapola". More than 75% students have hostel facilities. Most of University students desire to government jobs after the University education.